Análisis de corrientes de cortocircuito para el dimensionamiento de un interruptor de potencia a 13.8 kv entre la unidad generadora u1 y el transformador de potencia de 40 mva a 13.8/138 kv en la central hidroeléctrica Pucará CELEC E.P unidad de negocio hidroagoyan en el periodo 2015 - 2016 - Paucar Fonseca, Jairo Fabricio (2016)
The following research work was developed with the purpose of sizing and purpose a circuit breaker with its respective characteristics and the necessary parameters in EP CELEC Pucara Hydroelectric Business Unit Hidroagoyan to 13.8 kV generating unit U1. This work was done with the use of surveys as a research tool to collect real time information on current operating conditions which is working to join the National Interconnected System (SNI) to prove the formulated hypothesis. This work used ETAP 12.6.0 software as a standardized rules guide IEC (International Electrotechnical Commission) for the specifications of the electric flow under regular and irregular conditions….